Response of breeding and gestating sows to a dietary source of lactobacillus acidophilus - B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1971)
During the breeding period, adding the fermentation product (lactobacillus acidophilus) to the ration fed to gilts and sows made no difference in conception percentages. Nonsignificant differences was observed between the control group and the group receiving the additive in number of pigs born dead or alive and weight of pigs at 2 or 4 weeks of age.; Swine Day, Manhattan, KS, October 7, 1971
Keywords: Swine day; 1971; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 181; Swine; Lactobacillus acidophilus; Breeding sows; Gestation